The Value of foresight : the story of Thomas Jefferson - Johnson, Ann Donegan (La Jolla, CA : Value Comm., Inc Pub, 1997)
A biography of Thomas Jefferson emphasizing his lasting contributions to his country.
Keywords: Jefferson, Thomas, President U. S., 1743-1826; Presidents--United States-- Biography; Prudence